Use and legislation of Glyphosate in Mexico: healthcare, healthy environment and drinking water access. - Arizbeth Pérez-Martínez; Arely Vergara-Castañeda; Kytzia Esmeralda Mercado-Moreno; Christian Benítez-Núñez; Alma Cossette Guadarrama Muñoz (Nova Scientia)
This paper analyzes the status of legal regulation of the use of glyphosate in Mexico. To achieve this purpose, its use has been debated in constitutional obligations to human rights to health, the environment, and access to drinking water. Glyphosate is an agrochemical compound used as a main substance in the formulation of pesticides having a low toxicological level, and it is currently the most widely used herbicide worldwide. It is well known that many international organizations have reported that the use of glyphosate does not represent harm to health, if it is used properly and, in the concentration indicated in the regulations. However, glyphosate inhibits enzymatic production which is the key factor to the aromatic amino acid biosynthesis needed for vegetation growth, having a negative effect on the environment. Researchers have suggested an important risk to health by indirect glyphosate exposure, such as water and food polluted with glyphosate residues, which could develop diseases or health conditions such as skin irritations, gastrointestinal disorders, endocrine or hematological disrupters, etc. In Mexico, there are reports about the presence of glyphosate in food, particularly 30% of tortillas production in Mexico City presents glyphosate residues. For this reason, the Mexican government has decided to eliminate the use of glyphosate in crop fields by 2024.